2016
DOI: 10.1016/j.jenvrad.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

135Cs/137Cs isotopic composition of environmental samples across Europe: Environmental transport and source term emission applications

Abstract: (135)Cs/(137)Cs isotopic analyses represent an important tool for studying the fate and transport of radiocesium in the environment; in this work the (135)Cs/(137)Cs isotopic composition in environmental samples taken from across Europe is reported. Surface soil and vegetation samples from western Russia, Ukraine, Austria, and Hungary show consistent aged thermal fission product (135)Cs/(137)Cs isotope ratios of 0.58 ± 0.01 (age corrected to 1/1/15), with the exception of one sample of soil-moss from Hungary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
5
24
0
Order By: Relevance
“…Results from our group, Zheng et al [17] and Taylor et al [8] for one such material (IAEA-375) are [8] White triangles represent grass, bark, and moss samples analyzed by Shibahara et al [20] White dots A, B, and C represent particulate tape sample datapoints for hourly 137 Cs airborne concentrations given by Tsuruta et al [3] (see also Fig. 5) shown in Supplementary have not yet reported values for IAEA-375, personal communications between our group and Dr Shibahara have revealed that both our groups have made measurements that are within statistical agreement for the reference material IAEA-156 (with errors in the 4% 2σ range; exact results from our group on this material have been reported elsewhere [38] [8] for the J-village soil (which is located~30 km south of the FDNPP site). While a much larger set of analyses at known locations to the south is needed for definitive determination of the extent of homogeneity in the 135 Cs/ 137 Cs isotopic composition to the south/southwest of the FDNPP site, currently available 135 Cs/ 137 Cs isotope data from locations in this direction appear to have a consistent 135 Cs/ 137 Cs isotope ratio of~0.376 (which is slightly higher than the value of 0.34 ± 0.01 previous reported by Zheng et al for samples to the northwest [8] ).…”
Section: Validation Of the Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…Results from our group, Zheng et al [17] and Taylor et al [8] for one such material (IAEA-375) are [8] White triangles represent grass, bark, and moss samples analyzed by Shibahara et al [20] White dots A, B, and C represent particulate tape sample datapoints for hourly 137 Cs airborne concentrations given by Tsuruta et al [3] (see also Fig. 5) shown in Supplementary have not yet reported values for IAEA-375, personal communications between our group and Dr Shibahara have revealed that both our groups have made measurements that are within statistical agreement for the reference material IAEA-156 (with errors in the 4% 2σ range; exact results from our group on this material have been reported elsewhere [38] [8] for the J-village soil (which is located~30 km south of the FDNPP site). While a much larger set of analyses at known locations to the south is needed for definitive determination of the extent of homogeneity in the 135 Cs/ 137 Cs isotopic composition to the south/southwest of the FDNPP site, currently available 135 Cs/ 137 Cs isotope data from locations in this direction appear to have a consistent 135 Cs/ 137 Cs isotope ratio of~0.376 (which is slightly higher than the value of 0.34 ± 0.01 previous reported by Zheng et al for samples to the northwest [8] ).…”
Section: Validation Of the Methodssupporting
confidence: 53%
“…While Shibahara et al . (Kyoto University Research Reactor Institute, Osaka, Japan) have not yet reported values for IAEA‐375, personal communications between our group and Dr Shibahara have revealed that both our groups have made measurements that are within statistical agreement for the reference material IAEA‐156 (with errors in the 4% 2σ range; exact results from our group on this material have been reported elsewhere). Agreement between measurements made by our group, Shibahara et al ., and Zheng et al .…”
Section: Methodsmentioning
confidence: 99%
“…These values are significantly higher than those of the plant samples, as shown in Table 2. The 135 Cs/ 137 Cs isotopic ratio of IAEA-156 obtained in this study was in agreement with that of IAEA-373 obtained in this study and the reported data for IAEA-156 [25], within error; these values were used as the 135 Cs/ 137 Cs isotopic ratio of the nuclear material released in the accident at CNPP. The average analytical error was ∼0.1% for the 135 Cs/ 137 Cs isotopic ratio determined in a previous analysis of Cs in plant samples [2][3][4], while the analytical errors for the 135 Cs/ 137 Cs ratio in this study was higher than that of the previous study.…”
Section: Results Of Cs Analysis By γ-Spectrometry and Timssupporting
confidence: 90%
“…It was confirmed that the three-time method was required for the recovery of Cs from the soil samples in this study (except for samples OK01 and OK03) and the IAEA-156 and IAEA-373 standard reference materials. In the case of the one-time method, the observed mass spectra were influenced by impurities, as also observed by Snow and coworkers [25]. However, in the previous study [2][3][4], the analytical error for the plant sample data showed a weaker dependence on the concentration of 137 Cs; the magnitude of the error was also lower than that of the soil sample.…”
Section: Results Of Cs Analysis By γ-Spectrometry and Timssupporting
confidence: 64%
See 1 more Smart Citation